Policy Analysis of Healthy Community Movement (Germas) during Pandemi COVID-19 in Yogyakarta - Siswati, Tri; Widyawati, Herni Endah; Supriyati, Supriyati; Baiquni, Fahmi; Wardhani, Ratri; Rahmawati, Riadini (Jurnal Kebijakan Kesehatan Indonesia, 2023)
The social environment, including policies, is one of the instruments to encourage health promotion toward a healthy life, preventing and controlling COVID-19. This was to analyze the content, process, content and policy actors related toThe Healthy Community Movement (Germas) and the prevention of COVID-19 in Yogyakarta.We apply a-qualitative research of policy. We apply rapid assessment procedures (RAP) using focus group discussion (FGD) and desk review to observe various of policy from the government website. Research conducted in Yogyakarta from March to May 2021. Data was analysis by qualitative content analysis based on content, process, context, and actor categories. Results showed that policies related to Germas already exist at all levels, both national, provincial and district/city locally. According to policy content, Germas was movement to promote the culture/behavior of healthy living based on community empowerment, that were 7 points were physical activity, consuming fruits and vegetables, not smoking, not consuming alcoholic beverages, early detection and medical examination routine, clean healthy and lifestyle, and using toilet. Base on process, there were national, provincial, and local policy level. At the national level there was presidential instructions, regulations of the minister of national development planning, while governor's, regent’s policy at level province and region respectively. Locally, some policy regulate special context on COVID-19 preventing and controlling to increase awareness of the risk of transmission of COVID-19 infection in Yogyakarta. The policy actors were all of local government organizations, universities, CSR, and community. The conclusion is The Special Region of Yogyakarta already has many policies covering various sectors of life to support the implementation of Germas in the pandemic era and has been carried out by stakeholders, CSR, universities, and all of government